(untitled) (Experimental biology, 2016)
To improve pharmacodynamics and drug farmakokineshks alk is necessary to develop and obtain new forms nanokapsuls, the study of the basic biological and pharmacological properties to further carry out all the necessary tests. Currently delk have been actively used in clinical practice, due to its antioxidants properties, as well as the ability to bind molecules and prevents his participation in the processes of lipid peroxidation. Lipoic acid acts as an inhibitor. Llipoic acid has a high degree of safety related to its physiological nature, proved its efficacy and safet, which determines its relevance to medicine. Recent advances in biomedical science have created the prerequisites for the development of new approaches to the diagnosis and prevention of socially significant diseases of man and the development of original, high- performance drugs with reduced toxicity.